Knowledge, attitude and practice on food waste management among food vendors in Universiti Putra Malaysia, Serdang, Selangor - Naim, Mohd Nazli; Abdul Rahman, Haliza (Faculty of Medicine and Health Sciences, University Putra Malaysia, 2020)
Introduction: Malaysian produced about 38,000 tons of waste per day in 2017, and 15,000 tons of it was food waste. Objective: To determine the knowledge, attitude, and practice of food waste management among food vendors in Universiti Putra Malaysia (UPM), Serdang. Methods: Universal sampling has been conducted to the respondents who are all food vendors under UPM Holdings provision. In this study, a modified questionnaire has distributed online to 37 food vendors. Fisher’s Exact test was applied to determine the association among variables. Results: All respondents in UPM had a moderate level of knowledge, attitude, and practice on food waste management. The results highlighted that attendance in food waste management training has a significant association with food waste management (p<0.05, p=0.048). Furthermore, a significant association between age and practice on food waste management has also been identified (p<0.05, p=0.034). Conclusion: This study’s information has indicated that a food waste management training program is needed, in which UPM could cooperate with organisations to improve food waste management.